Object categorization by wild-ranging birds in nest defence - Nováková, Nela; Veselý, Petr; Fuchs, Roman (Animal cognition, 2020)
Despite object categorization being an important ability for the survival of wild animals, the principles behind this ability have been only scarcely studied using wild-ranging, untrained animals. Reiterating our previous study undertaken with wild-ranging titmice on winter feeders (Nováková et al. Behav Process 143:7-12, 2017), we aimed to test two hypotheses of object recognition proposed by animal psychology studies: the particulate feature theory and recognition by components in the methodological paradigm of nest defence. We tested whether the parents of the red-backed shrike (Lanius collurio) recognize the dummies of the common kestrel (Falco tinnunculus), which is a potential predator of large chicks or fledglings, as a threat in case when their body parts are scrambled. The kestrel dummy was presented with the head at the top, in the middle, and at the bottom of the body. We showed that the shrikes did not consider dummies of a kestrel with an inappropriately placed head as a threat to the nest and attacked it equally scarcely as the harmless control. These results support the theory of recognition by components, presuming that the mutual position of body parts is essential for appropriate recognition of the object. When the body parts were scrambled, most of shrikes were not able to identify the kestrel in such an object despite all local features (eye, beak, colouration, and claws) being present. Nevertheless, shrikes did not consider the scrambled dummies as completely harmless, because they fed their chicks in their presence significantly less often than in the presence of harmless control.
Keywords: Passeriformes; Recognition, Psychology; Animals; Falconiformes; rozpoznávání (psychologie); roční období; Seasons; zvířata; Animals, Wild; divoká zvířata